2000
DOI: 10.1677/joe.0.1650493
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-alpha stimulates proliferation of mammotrophs and corticotrophs in the mouse pituitary

Abstract: Oestrogen stimulates the proliferation of pituitary cells. The present study was designed to clarify the involvement of transforming growth factor-(TGF-) in the oestrogen-induced growth of mouse pituitary cells in vitro. Anterior pituitary cells obtained from ICR male mice were cultured in a primary serum-free culture system. Proliferation of pituitary cells was detected by monitoring the cellular uptake of bromodeoxyuridine. Secretory cell types were immunocytochemically determined. Treatment with TGF-(0·1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 43 publications
1
34
0
1
Order By: Relevance
“…However, physiological growth factors which are involved in steroid hormone-induced proliferation of the stromal cells remains to be determined. Interestingly, in a study of pituitary growth, we found that TGF-α is a mediator of estrogen-induced proliferation of mammotrophs, since treatment of mouse pituitary cells with antisense TGF-α oligodeoxynucleotide or anti-TGF-α antibodies inhibited estrogen-induced proliferation of mammotrophs (Oomizu et al, 2000;Takahashi et al, 2002;Sharma et al, 2003). These results altogether suggest that estrogen-induced growth of various tissues is controlled by a common mechanism of an autocrine or paracrine action of growth factors.…”
Section: Discussionmentioning
confidence: 86%
“…However, physiological growth factors which are involved in steroid hormone-induced proliferation of the stromal cells remains to be determined. Interestingly, in a study of pituitary growth, we found that TGF-α is a mediator of estrogen-induced proliferation of mammotrophs, since treatment of mouse pituitary cells with antisense TGF-α oligodeoxynucleotide or anti-TGF-α antibodies inhibited estrogen-induced proliferation of mammotrophs (Oomizu et al, 2000;Takahashi et al, 2002;Sharma et al, 2003). These results altogether suggest that estrogen-induced growth of various tissues is controlled by a common mechanism of an autocrine or paracrine action of growth factors.…”
Section: Discussionmentioning
confidence: 86%
“…Cyclin D1 overexpression that is the functional characteristic of nuclear EGFR is not featured in human corticotrophinomas (10). Nevertheless, nuclear EGFR was detected by immunofluorescence in this pituitary tumor subtype (50). Nuclear EGFR deubiquitination by nuclearly-located USP8 mutants may regulate the nuclear function of EGFR.…”
Section: The CD Usp8 Mutants Affect Egfr Downregulation and Acth Syntmentioning
confidence: 88%
“…In primary cultures of male mouse anterior pituitaries, EGF treatment enhanced BrdU uptake in ACTH-(as well as in PRL-) immunopositive cells, but not in other pituitary cell subpopulations (37). The EGFR inhibitor RG-13022 decreased the percentage of BrdU labeled cells immunoreactive for ACTH (and PRL), providing functional evidence for the presence of active receptors on corticotroph (and lactotroph) populations (50).…”
Section: Egfr and Corticotroph Functionmentioning
confidence: 94%
“…It is well known that PRL cells have the ability to replicate DNA and to divide in rat and mouse pituitary glands in vivo and in vitro in response to estrogen and various growth factors (Takahashi et al ., 1984;Oishi et al ., 1993;Oomizu et al ., 2000). In contrast, it is evident from the present study that PRL cells of GH3 cells are unable to replicate DNA molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The highest mitotic activity of PRL cells is observed at estrus in the female rat pituitary (Takahashi et al ., 1984;Oishi et al ., 1993). As estrogen treatment stimulates the proliferation of PRL cells (Lloyd et al ., 1975;Takahashi and Kawashima, 1987;Oomizu et al ., 2000), the high proliferating activity of PRL cells is caused by the increase in estrogen secretion during the proestrous and estrous days. Thus, it is evident that PRL cells are generated from preexisting PRL cells through mitosis under estrogenic stimulation (self-duplication) in vivo .…”
Section: Introductionmentioning
confidence: 99%